Analisis Asuhan Keperawatan Dengan Intervensi Workout At Home Terhadap Penurunan Berat Badan Pada Remaja Obesitas Di RW 07 Grogol Depok - Fitrianih Azzahra (2023)
Obesity is a problem that must be addressed because it can affect people of all ages, including children, adults, and the elderly. Obesity that occurs in adolescents can interfere with adolescent body image. Several interventions are believed to help reduce weight in obese adolescents. Workout at home is one of the interventions that has been proven to reduce weight. This nursing care analysis aims to determine the effectiveness of workout at home on weight loss in obese adolescents. This author aims to carry out a workout at home management of weight loss in obese adolescents. This intervention was given to two obese adolescents at RT 004/07 and was carried out 4 times a week and was carried out for 4 weeks. The results of the implementation for 4 weeks showed that there was a weight loss of 3.7 kg for the first client and 3.8 kg for the second client. The results of the paired t-test analysis showed a p-value <0.05 so it can be concluded that there is an effect of the workout at home intervention on weight loss in obese adolescents. Community nurses are expected to be able to use body weight training interventions as one of the interventions for weight loss in adolescents with obesity Keywords: Adolescents, Workout At Home, Obesity